Pengaruh Budaya Organisasi, Komunikasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Di Kantor Pelayanan Pajak - Hermawan, Wahyu; Darmawan, Didik; Yulianto, Yulianto; Marpaung, Rahmad Yani; Purtaminingsih, Endang; Suprayitno, Eddi; Sadly, Effendy; Pane, Sri Gustina (Graha Mitra Edukasi, 2024)
This research aims to determine the influence of organizational culture, communication and job satisfaction partially and simultaneously on employee performance at the Binjai Pratama Tax Service Office. The research was conducted at the Binjai Primary Tax Service Office Jalan Jambi No.1, West Rambung, South Binjai., Binjai City, North Sumatra Province, postal code 20722, with a population of 101 people, and a research sample of 50 people. Data collection was carried out by interviews, questionnaires and documentation. The data analysis technique used is multiple regression analysis using the IMB Statistics for Product and Service Solution (SPSS) computer program version 24. Based on the results of the analysis, it is found that organizational culture has a positive and significant effect on the performance of employees of the Binjai Pratama Tax Service Office, this is supported by the results of the analysis t count > t-table (2.106 > 2.014) at n = 50 at the 95% significance level. Communication has a positive and significant effect on the performance of the Binjai Pratama Tax Service Office employees, this is supported by the analysis of t count > t-table (8.186 > 2.014) at n = 50 at a significance level of 95%. Job satisfaction has a positive and significant effect on the performance of employees at the Binjai Pratama Tax Service Office, this is supported by the analysis of t count > t-table (4.107 > 2.014) at n = 50 with a significance level of 95%. The F-count value > F table (50.249 > 2.81), this states that together (multiple) there is a positive and significant influence of organizational culture, communication and job satisfaction on the performance of the Binjai Pratama Tax Service Office employees. Thus the hypothesis proposed is accepted as true.